(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Gli interventi contro i Testimoni di Geova nella Federazione Russa - 2. La presenza storica dei Testimoni di Geova nel Paese - 3. La libertà religiosa nella normativa dell’Unione Sovietica - 4. Le leggi sulla libertà di coscienza degli anni ’90 - 5. La legislazione “anti estremismo” e antiterrorismo - 6. Considerazioni conclusive. “Anti-extremism” Legislation and Religious Freedom in the Russian Federation. The case of Jehovah’s Witnesses ABSTRACT: The application of "anti-extremism" legislation to minority religious groups in the Russian Federation has led to a progressive institutional tightening of the persecution and heavy discrimination, especially against Jehovah’s Witnesses. Although many of these legislative instruments have existed for over a decade, the Russian government has only recently begun to use them in sustained campaigns designed to punish or exclude "non-traditional" religions and movements. In the specific case of Jehovah’s Witnesses, these measures have taken on the purpose of delegitimising an entire community, solely because of the religious faith being persecuted, with accusations ranging from missionary activity to offending the religious feelings of believers. Overall, these interventions are part of a wider process of ideological control over society, aimed at curbing, if not stifling, the forces of political and religious dissent. It is well known that secularism is based on two fundamental principles: the inviolability of human rights, which constitute the prodrome of political power and therefore of the State, and, secondly, the importance of a culture and institutions that guarantee the effectiveness of pluralism. The analysis of the Russian history is, in this sense, an important perspective because it calls into question the European model of recognition and guarantee of religious pluralism.